Edoxaban versus Warfarin in Patients with Atrial Fibrillation at the Extremes of Body Weight: An Analysis from the ENGAGE AF-TIMI 48 Trial - Boriani, Giuseppe; Ruff, Christian T.; Kuder, Julia F.; Shi, Minggao; Lanz, Hans J.; Antman, Elliott M.; Braunwald, Eugene; Giugliano, Robert P. (Thrombosis and Haemostasis, 2020)
Background The effects of anticoagulants at extremes of body weight (BW) are not well described. The aim of this study was to analyze the pharmacokinetics/pharmacodynamics and clinical outcomes in patients randomized to warfarin, higher dose edoxaban (HDER), and lower dose edoxaban (LDER) regimens at extremes of BW in ENGAGE AF-TIMI 48.Methods and Results We analyzed three BW groups: low BW (LBW: <5th percentile, ≤55 kg, N = 1,082), middle BW (MBW: 45th–55th percentile, 79.8–84 kg, N = 2,153), and high BW (HBW: >95th percentile, ≥120 kg, N = 1,093). In the warfarin arm, LBW patients had higher rates of stroke/systemic embolism (SSE: 6.5 vs. 4.7 in MBW vs. 1.6% in HBW, Ptrend < 0.001), major bleeding (MB: 9.3 vs. 7.7 vs. 6.5%, Ptrend = 0.08), and worse net clinical outcome of systemic embolic event, MB, or death (31.5 vs. 19.1 vs. 16.0%, Ptrend < 0.0001). The time-in-therapeutic range with warfarin was lowest in LBW patients (63.0 vs. 69.3 vs. 70.1% patients, Ptrend < 0.001). The pharmacokinetic/pharmacodynamic profile of edoxaban was consistent across BW groups. The risk of SSE was similar between HDER and warfarin for each of the three weight groups (Pint = 0.52, Pint-trend = 0.86). MB was reduced by LDER versus warfarin (Pint = 0.061, Pint-trend = 0.023), especially in LBW patients. Net clinical outcomes were improved by HDER versus warfarin (Pint = 0.087, Pint-trend = 0.027), especially in LBW patients.Conclusion Patients with LBW in ENGAGE AF-TIMI 48 had in general a more fragile clinical status and poorer international normalized ratio control. The pharmacokinetic/pharmacodynamic profile of edoxaban was consistent across extremes of BW, resulting in similar efficacy compared with warfarin, while major or clinically relevant non-MB and net outcomes were most favorable with edoxaban as compared to warfarin in LBW patients.
Keywords: anticoagulation; atrial fibrillation; edoxaban; factor Xa; pharmacokinetics; weight; underweight